THE RELATION BETWEEN LEARNING STYLE, INDEPENDENCE LEARNING, PARENTS’ ATTENTION AND MATHEMATICS LEARNING OUTCOMES OF GRADE X VISUAL COMMUNICATION DESIGN STUDENTS OF SMK - Rosi Anista; Edi Prajitno (Universitas Ahmad Dahlan, 2018)
Mathematics students are learning outcomes associated with many factors. Learning style, independence learning, and parents’ attention are some of the factors allegedly related to learning outcomes. The researches are intended to know about is there any positive correlation and significance or not between learning style, independence learning, parents’ attention and mathematics learning outcomes of grade X Visual Communication Design students of State Vocational High School 5 Yogyakarta (SMK Negeri 5 Yogyakarta) in the even semester of the academic year of 2016/2017. The population in this research was the student's grade X Visual Communication Design of SMK Negeri 5 Yogyakarta of 2016/2017, consisting of class X Visual Communication Design A and class X Visual Communication Design B, totaling 62 students. Samples were taken from X Visual Communication Design B as the research sample class and random sampling technique. The writer uses a questionnaire method to collect the learning style, independence learning, parents’ attention, and test method to get the resulting learning of math. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed a positive and significant relationship between learning style, independence learning, parents’ attention with mathematics learning outcomes of grade X Visual Communication Design students of SMK Negeri 5 Yogyakarta in the even semester of the academic year of 2016/2017. It is showed by Fcount Ftable is 6,2085 > 2.9500 with R = 0.6320 and R2 = 0.3994 with ,with RC = , RC = and RC = 19,9183 , EC = , EC = and EC = .